Exploring the Spatial Perception of Risk in Portugal by Students of Geography. Issue 5 (2nd September 2020) - Nunes, Adélia; Martins, Bruno; Azevedo, Maria
Abstract: This study set out to assess the ability of year nine students to identify and classify the most likely natural and mixed risks, both on a national scale and within the Metropolitan Area of Porto (AMP). We also sought to assess the respective spatial perception of different risks at regional level. For this purpose, a questionnaire was applied and the results show that the students classified the risk of forest fire as the most likely to occur, both nationwide and in all AMP municipalities, with a rating ranging from high to moderate, respectively. In spatial terms, they clearly define the areas most vulnerable to each of the listed risks, identifying forest fires and heat waves as most likely to occur, and the northern and coastal regions of Portugal where the greatest number of risks are concentrated.